Distress Tolerance and Mental Health Problems among University Students: Distress Tolerance and Mental Health - Anwar, Nida; Shahzadi, Maryam; Shahzadi, Mafia; Khanum, Sanober; Imtiaz, Madeeha (Pakistan Journal of Health Sciences, 2024)
Academic stress is one of the major reasons which influence students’ mental health. Tolerance significantly contributes to managing academic pressure, a sense of competence, and parental and social expectations while lacking causes mental health issues. Objective: To explore the relationship between distress tolerance and mental health problems among university students. Methods: 500 students from different universities of Faisalabad. The age range of the participants covered the years 20 to 40. The sample was taken using a purposive sampling technique. The following measures were used to assess the findings i.e. demographic form, distress tolerance scale, depression, anxiety and stress scale were used to explore the relationship between distress tolerance and mental health problems among university students. Results: Findings indicate a significant relationship between distress tolerance and depression (r = -.182, P < 0.01), distress tolerance and anxiety (r = -.243, P < 0.01), and distress tolerance and stress (-.252, P < 0.01) among university students. Conclusions: It is concluded that the level of tolerance significantly helps to overcome daily life stressors, anxieties, and depressive symptoms among the students.